2017
DOI: 10.1007/s00590-017-1969-x
|View full text |Cite
|
Sign up to set email alerts
|

A modified minimally invasive technique for intra-articular displaced calcaneal fractures fixed by transverse and axial screws

Abstract: The management of displaced, intra-articular calcaneal fracture represents a surgical challenge to even an experienced orthopedic surgeon. Plate osteosynthesis using an extended lateral approach is complicated by soft tissue problems, while those treated by closed reduction and percutaneous pinning cannot address all the intra-articular fragments sufficiently. The objective of our study is to evaluate restoration of subtalar joint and long-term functional outcomes in intra-articular displaced calcaneal fractur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The significant benefits brought by temporary LRS external fixation in the effective maintenance of fracture fragments were the reduced use of fluoroscopy (20 times on average) and consequently less total operation time (81.68 min on average). This led to a lower rate of surgical complications, according to the very limited data reported 22,23 . Finally, the LRS external fixation in our surgical protocol was used only intraoperatively and was removed by the end of surgery; therefore, complications were caused by long‐term wearing of the external fixator, such as pin tract infection, skin strain injury, joint stiffness, edema, traction needle rupture, pain 9–14 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The significant benefits brought by temporary LRS external fixation in the effective maintenance of fracture fragments were the reduced use of fluoroscopy (20 times on average) and consequently less total operation time (81.68 min on average). This led to a lower rate of surgical complications, according to the very limited data reported 22,23 . Finally, the LRS external fixation in our surgical protocol was used only intraoperatively and was removed by the end of surgery; therefore, complications were caused by long‐term wearing of the external fixator, such as pin tract infection, skin strain injury, joint stiffness, edema, traction needle rupture, pain 9–14 …”
Section: Discussionmentioning
confidence: 95%
“…This led to a lower rate of surgical complications, according to the very limited data reported. 22,23 Finally, the LRS external fixation in our surgical protocol was used only intraoperatively and was removed by the end of surgery; therefore, complications were caused by long-term wearing of the external fixator, such as pin tract infection, skin strain injury, joint stiffness, edema, traction needle rupture, pain. [9][10][11][12][13][14] Evaluate the Efficacy of LRS Assisted Minimally Invasive Reduction Other methods of external fixation have also been reported.…”
Section: The Technical Points Of Using Lrs Intraoperativelymentioning
confidence: 99%
“…The mean pre-operative angle was 2.8° (range from − 38° to 24°), and post-operatively it was 19.4° (range from 5° to 49°), but they did not give a correlation between radiographic correction and functional outcomes. Kapil Mani et al [ 38 ], who used MIS with cannulated screws for treatment of DIACFs, reported the pre-operative calcaneal length, height, width, Böhler’s angle, and Gissane angle were significantly improved after surgery, but they did not give a correlation between radiographic correction and functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Longer duration was needed for union in the K-wire group ( P -value = 0.016). Kapil Mani et al [ 38 ] obtained union at 11.06 ± 1.82 (range, 8–16) weeks. Arora et al [ 23 ] obtained union at a mean of 8.2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] To reduce these complications, the use of minimal invasive techniques is increasing. However, disadvantages of these techniques, such as wound infection, impingement, tendinitis, etc., have also been reported [ [5] , [6] , [7] , [8] , [9] , [10] , [11] ].…”
Section: Introductionmentioning
confidence: 95%